Using Subject Positioning Theory to Investigate Reading Engagement among University Students - Salmah Anisah Abu Hassan; Norkhairi bin Ahmad (Tell : Teaching of English Language and Literature Journal, 2022)
This study sets out to investigate the magnitude of reading engagement by technical engineering undergraduates. Purposive samples in the form of six bachelor’s degree students were chosen based on the observed active roles as class representatives and as active learners in the English course that they have previously taken. Two chapters from a compulsory textbook of a mandatory course from the undergraduates’ programme called Innovation Management were chosen to explore their subject positioning and reading engagement aspect. The undergraduates were requested to activey read, interact and scribble  notes if necessary during reading while their engagement via think aloud protocol were recorded. The recordings were transcribed and analysed for evidence of subject positioning  and knowledge processing with inter rater and expert verifications on the identified themes. The findings show that the uundergraduates actively undertake subject positioning to align and disalign with subject matter materials and information put forth by the author of the textbook as evidence of moderate to active reading engagement and knowledge processing. Input from previous reading, general knowldge, current experience and previous work experience intertwine in functioning as sources of the subject positioning and knowledge processing during the reading engagements. The findings are significant in raising awareness among educators on the need to cultivate active reading engagement and to devise training for undergraduates on strategies for active reading engagement. These recommended efforts from this study will yield great benefits for undergraduates in their learning curve at the academia.